Determination of Chemical, Physical and Biological Characteristics of Some Pekmez (Molasses) From Turkey - Aliyazicioglu, Rezzan; Kolayli, Sevgi; Kara, Meryem; Yildiz, Oktay; Osman Sarikaya, Ali; Cengiz, Sevil; Er, Fatih (Asian Journal of Chemistry, 2010)
Antioxidant capacity, chemical and physical properties of 6 certificated and 1 uncertificated pekmez (molasses) samples of Turkish varieties were analyzed. All pekmez samples had similar chemical compositions. Total phenolic contents varied from 138 to 243 mg of gallic acid equivalents/100 g samples. The apricot pekmez had the highest phenolic content (243 ± 16), while the carob pekmez exhibited the highest DPPH (0.08 ± 0.01 mg g-1) radical scavenging activity. DPPH radical scavenging activity was also found to be related to concentrations of the samples. Especially, selenium and other minerals content were found slightly higher in grape pekmez than the others. Present results showed that all the certificated and uncertificated pekmez samples had no any risk in public health and besides their high content of sugar. Each pekmez had antioxidant and high amount of polyphenols and minerals.